Early and midterm results of valve-sparing aortic root reconstruction with a bovine pericardium patch for patients with acute type a aortic dissection - Yang, Jue; Li, Xin; Wu, Meifen; Wu, Jinlin; Chen, Zerui; Sun, Tucheng; Fan, Ruixin; Yu, Changjiang (Frontiers in Cardiovascular Medicine, 2022)
Objectives: We evaluated the feasibility, effectiveness, and safety of valve-sparing aortic root reconstruction with a bovine pericardium patch for patients with acute type A aortic dissection (ATAAD). Methods: From January 2016 to January 2021, 895 consecutive patients with ATAAD received surgical treatment at our hospital. After applying our exclusion criteria, 508 patients were included in this research. Based on the attending surgeon’s judgment and preference, 192 patients underwent our novel surgical novel surgical technique of valve-sparing aortic root reconstruction (repair group [RG]) and 316 patients underwent the Bentall procedure (Bentall group [BG]). Results: In the RG, the early mortality rate was 4.2% (8/192). In the BG, the early mortality rate was 5.1% (16/316). There were no significant differences between groups. The incidence of postoperative renal failure in the BG was significantly higher than that in the RG. The mean follow-up time was 2.93 years (standard deviation, ±1.38 years). There were no significant differences between groups regarding ATAAD-related mortality and reoperation. In the RG, the rate of freedom from aortic root reoperation at 5 years was 98.2%, and the grade of aortic regurgitation 6 months later was significant less than that before surgery, and it did not worsen during later follow-up. Conclusions: Valve-sparing aortic root reconstruction with a bovine pericardium patch can be successfully performed for selected patients with ATAAD and is associated with low in-hospital and late mortality rates and low root reoperation rates during early and midterm follow-up.